SP0092 Osteoporosis. Whom, When and How to Treat. (10th June 2014) - Peris, P.
Abstract : The evaluation and treatment of osteoporosis differ depending on several conditions such as the associated risk factors for the development of osteoporosis and fragility fractures, gender, age and menopausal status of the individual, and the presence of other secondary associated processes, among others. In addition, some types of secondary osteoporosis, such as glucocorticoid induced osteoporosis, present fractures with relatively higher bone mineral density values, whereas other metabolic bone diseases, such as osteomalacia, can easly be misdiagnosed with this condition. All these data should be taken into account when evaluating the diagnosis and treatment of these patients. Besides general measures, the pharmacological management of osteoporosis, including the type of antiosteoporotic drug, administration route, optimal treatment duration and monitoring, depend on the characteristics of the patient, the fracture risk and the type of treatment. Thus, whereas bisphosphonates are commonly used in postmenopausal osteoporotic women and men, they should be used with caution in premenopausal women. Moreover, additional non-pharmacologic therapies, such as the use of percutaneous vertebroplasty for the treatment of painful vertebral fractures need appropriate patient selection. In summary, the therapeutic approach of osteoporosis managment involves several aspects that include the identification of individuals at risk of fracture, the correction of modifiable risk factors and, when indicated, the selection of the most appropriate drug therapy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6220